Complicated Clinical Course in Incipient Gigantism Due to Treatment-resistant Aryl Hydrocarbon Receptor–Interacting Protein–mutated Pediatric Somatotropinoma - Selveta Sanne van Santen, MD, MSc; Adrian F. Daly, MB, BCh, PhD; Michael Buchfelder, MD, PhD; Roland Coras, MD; Yining Zhao, MD, MSc; Albert Beckers, MD, PhD; Aart Jan van der Lely, MD, PhD; Leo J. Hofland, MD, PhD; Rutger K. Balvers, MD, PhD; P. van Koetsveld, Ing; Marry Marrigje van den Heuvel-Eibrink, MD, PhD; Sebastian Johannes Cornelis Martinus Maria Neggers, MD, PhD (AACE Clinical Case Reports, 2022)
Background: Our objective was to describe the clinical course and treatment challenges in a very young patient with a pituitary adenoma due to a novel aryl hydrocarbon receptor–interacting protein (AIP) gene mutation, highlighting the limitations of somatostatin receptor immunohistochemistry to predict clinical responses to somatostatin analogs in acromegaly. Case Report: We report the case of a 7-year-old boy presenting with headache, visual field defects, and accelerated growth following failure to thrive. The laboratory results showed high insulin-like growth factor I (IGF-I) (standardised deviation scores ( +3.49) and prolactin levels (0.5 nmol/L), and magnetic resonance imaging identified a pituitary macroadenoma. Tumoral/hormonal control could not be achieved despite 3 neurosurgical procedures, each time with apparent total resection or with lanreotide or pasireotide. IGF-I levels decreased with the GH receptor antagonist pegvisomant. The loss of somatostatin receptor 5 was observed between the second and third tumor resection. In vitro, no effect on tumoral GH release by pasireotide (with/without cabergoline) was observed. Genetic analysis revealed a novel germline AIP mutation: p.Tyr202∗ (pathogenic; class 4). Discussion: In vitro response of tumor tissue to somatostatin may better predict tumoral in vivo responses of somatostatin analogs than somatostatin receptor immunohistochemistry. Conclusion: We identified a novel pathologic AIP mutation that was associated with incipient acrogigantism in an extremely young patient who had a complicated course of disease. Growth acceleration can be masked due to failure to thrive. Tumoral growth hormone release in vivo may be predicted with in vitro exposure to somatostatin receptor analogs, as it cannot be assumed that all AIP-mutated somatotropinomas respond well to pasireotide.